Adaptasi Kerangka Hukum Korporasi untuk Mendukung Pertumbuhan Ekosistem Startup di Indonesia (Lex Mercatoria, 2025)
The objective of this research is to examine the adaptation of the corporate legal framework to support the growth of the startup ecosystem in Indonesia. This study employs a normative (doctrinal) legal research method focusing on the analysis of written legal norms to identify legal vacuums and inconsistencies between regulations and startup business practices. The research data consists of secondary data obtained through library research. Data analysis was conducted qualitatively and normatively through four stages. The research findings are as follows: (1) Indonesia's corporate legal framework as regulated in the Limited Liability Company Law (UUPT) demonstrates substantial incompatibility with the needs of fast-paced and innovative startup business models and financing mechanisms. (2) Indonesian startups face systemic and multidimensional corporate legal challenges in three critical aspects. (3) An agile and supportive corporate legal adjustment model requires comprehensive reform through the establishment of special regulations.Keywords: Adaptation; Legal Framework; Corporate; Startup